2021
DOI: 10.5194/acp-2021-49
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid transformation of ambient absorbing aerosols from West African biomass burning

Abstract: Abstract. Seasonal biomass burning (BB) over West Africa is a globally significant source of carbonaceous particles in the atmosphere, which have important climate impacts but are poorly constrained. Here, the evolution of smoke aerosols emitted from flaming-controlled burning of agricultural waste and wooded savannah in the Senegal region was characterized over a timescale of half-day advection from source during the MOYA-2017 (Methane Observation Yearly Assessment-2017) aircraft campaign. Plumes from such fi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Barker et al [42] found these fires had mean emission factors units (in g per kg of dry fuel) of 1.8 ± 0.6 for CH 4 , 1630 ± 21.4 for CO 2 and 67 ± 14 for CO, with a mean combustion efficiency of 0.94 ± 0.01, and obtained a δ 13 C CH 4 value of about −34‰ from all regional sources. Wu et al [43] provide further details about the FAAM flights and sampling for the MOYA project, and report aerosol measurements and chemical transformations in biomass burning plumes sampled in the region.…”
Section: Results (A) Senegal Fires-casamance Dry Forestmentioning
confidence: 99%
See 2 more Smart Citations
“…Barker et al [42] found these fires had mean emission factors units (in g per kg of dry fuel) of 1.8 ± 0.6 for CH 4 , 1630 ± 21.4 for CO 2 and 67 ± 14 for CO, with a mean combustion efficiency of 0.94 ± 0.01, and obtained a δ 13 C CH 4 value of about −34‰ from all regional sources. Wu et al [43] provide further details about the FAAM flights and sampling for the MOYA project, and report aerosol measurements and chemical transformations in biomass burning plumes sampled in the region.…”
Section: Results (A) Senegal Fires-casamance Dry Forestmentioning
confidence: 99%
“…Wu et al . [ 43 ] provide further details about the FAAM flights and sampling for the MOYA project, and report aerosol measurements and chemical transformations in biomass burning plumes sampled in the region.
Figure 1.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At shorter wavelengths, a parameterization that results in lower BrC absorption at low BC:OA (WE‐CAN) and higher BrC absorption at higher BC:OA (ORACLES‐2016/CLARIFY) would better match these observations. It is possible that we are not representing another potential explanation for the different absorption of BrC in the two regions: recent work has shown that under conditions with very high primary BC:OA ratios from biomass combustion (such as savanna burning in Africa), a first stage of BrC enhancement happens after emission, owing to formation of highly absorbing SOA, and before whitening (the whitening may result from less‐absorbing SOA formation in those experiments) (Cappa et al., 2020; Wu et al., 2021).…”
Section: Impact Of Alternate Brc Absorption Parameterizationsmentioning
confidence: 99%
“…A low-pressure water-based condensation particle counter (WCPC model 3786-LP) was connected to a TSI 3081 differential mobility analyser (DMA). Following the schemes developed by Zhou (2001), the SMPS data were inverted based on a ~1 min averaging time when aerosol mass concentrations from the AMS and SP2 varied less than 30%.…”
Section: Airborne Measurementsmentioning
confidence: 99%